2022
DOI: 10.1039/d2ob01662a
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium catalysed intramolecular benzannulation for the formation of tetracyclic carbazoles

Abstract: Rhodium catalyzed alkyne-tethered intramolecular annulation has been demonstrated for the synthesis of tetracyclic carbazole skeletons and successfully attained a series of five to eight-membered pyrido[3,2,1-jk]carbazoles. The present atom economic annulation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“… 66 Kumar et al reported the synthesis of tetracyclic carbazoles via an intramolecular benzannulation of alkyne-tethered indoles catalyzed with rhodium acetate in the presence of an oxidant and solvent. 67 The reaction conditions were optimized by screening different catalysts and solvents by altering their concentration. The intramolecular benzannulation of ethyl 3-(indol-3-yl)acrylate tethered with alkyne 42 was performed by employing 5 mol% of rhodium acetate, 2 mol% of copper bromide in dimethyl acetate to obtain the annulated product 43.…”
Section: Synthesis Of Carbazole Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“… 66 Kumar et al reported the synthesis of tetracyclic carbazoles via an intramolecular benzannulation of alkyne-tethered indoles catalyzed with rhodium acetate in the presence of an oxidant and solvent. 67 The reaction conditions were optimized by screening different catalysts and solvents by altering their concentration. The intramolecular benzannulation of ethyl 3-(indol-3-yl)acrylate tethered with alkyne 42 was performed by employing 5 mol% of rhodium acetate, 2 mol% of copper bromide in dimethyl acetate to obtain the annulated product 43.…”
Section: Synthesis Of Carbazole Nucleusmentioning
confidence: 99%
“…In the final step, the target compound was synthesized by reductive elimination of intermediate C ( Scheme 11 ). 67 The exploitation of stable bisalkynol 44, obtained from N , N -bis(2- bromoallyl)amines, for a gold-catalyzed back-to-front approach to access carbazoles 45 via a double benzannulation strategy was proposed by Muñoz-Torres et al in 2021. 68 The reaction proceeded in the presence of 5 mol% of NaAuCl 4 ·2H 2 O in DCM which induced double benzannulation to give substituted carbazoles in 60–85% yields ( Scheme 12 ).…”
Section: Synthesis Of Carbazole Nucleusmentioning
confidence: 99%